2015
DOI: 10.1155/2015/490842
|View full text |Cite
|
Sign up to set email alerts
|

GDF-15 as a Target and Biomarker for Diabetes and Cardiovascular Diseases: A Translational Prospective

Abstract: Growth differentiation factor-15 (GDF-15) is a stress responsive cytokine. It is highly expressed in cardiomyocytes, adipocytes, macrophages, endothelial cells, and vascular smooth muscle cells in normal and pathological condition. GDF-15 increases during tissue injury and inflammatory states and is associated with cardiometabolic risk. Increased GDF-15 levels are associated with cardiovascular diseases such as hypertrophy, heart failure, atherosclerosis, endothelial dysfunction, obesity, insulin resistance, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
338
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 376 publications
(356 citation statements)
references
References 109 publications
12
338
0
6
Order By: Relevance
“…Currently the number of accepted surrogates for assessment of new therapies and their utility in predicting response to therapy are relatively limited. Novel biochemical biomarkers 35 and new imaging methods 36 that have been shown to be mediators of risk in cardiovascular disease have also been proposed as measures of therapeutic efficacy. Identification of novel and accurate biomarkers that could serve as surrogate end points would facilitate rapid phase II development, including dose finding, and thereby reduce the time required to decide to proceed to the all-important phase III trial necessary to determine safety, 37 or to halt a development program and thereby minimize expenditure on ineffectual therapies.…”
Section: Identification Of More Meaningful Surrogate End Pointsmentioning
confidence: 99%
“…Currently the number of accepted surrogates for assessment of new therapies and their utility in predicting response to therapy are relatively limited. Novel biochemical biomarkers 35 and new imaging methods 36 that have been shown to be mediators of risk in cardiovascular disease have also been proposed as measures of therapeutic efficacy. Identification of novel and accurate biomarkers that could serve as surrogate end points would facilitate rapid phase II development, including dose finding, and thereby reduce the time required to decide to proceed to the all-important phase III trial necessary to determine safety, 37 or to halt a development program and thereby minimize expenditure on ineffectual therapies.…”
Section: Identification Of More Meaningful Surrogate End Pointsmentioning
confidence: 99%
“…CV biomarkers may contribute to improved prediction of CV mortality and CAD incidences in T2DM, but novel clinical data are required to understand what is critical numerous and combinations of markers are enough to increase risk stratification [83]. Measurement of serum levels of hs-CRP, galectin-3, NPs, and hs-cTnT probably allows the identification of T2DM patients at risk of CV events, although the predictive role of other cardiac biomarkers, i.e., soluble ST2, GDF-15, FGF-23 is not still understood [74,84]. Future directions are associated with discovering of novel biomarkers and optimal combinations of recently used markers to provide additional prognostic information beyond what is available with other traditional CV risk factors.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, GDF15 inhibits c-Jun N-terminal kinase, Bcl-2-associated death promoter, and epidermal growth factor receptor, as well as activates various intracellular signaling pathways, i.e., Smad, endothelial nitric oxide (eNO) synthase, phosphoinositide 3-kinase, and serine/threonine kinase. The final result of this interrelation is suppression of both tumor necrosis factor alpha and IL-6 synthesis, protect of pressureinduced cardiac hypertrophy, improvement of vascular integrity, and increasing cardiomyocyte and endothelial cell viability [74].…”
Section: Copeptinmentioning
confidence: 99%
“…cardiac hypertrophy, HF, atherosclerosis, stable coronary artery disease, myocardial infarction, as well as in hypertension, diabetes mellitus, abdominal obesity, chronic kidney disease, and malignancy [22][23][24]. Recent clinical studies have shown that GDF-15 independently predicted allcause mortality rate and CV death rate in patients with coronary artery disease, atrial fibrillation and HFpEF and HFrEF [24,25]. Moreover, GDF-15 has able to identify a vulnerable subjects in general population without known CV disease, prediabetes and diabetes mellitus [23].…”
Section: Introductionmentioning
confidence: 99%
“…Contrary, GDF-15-related recruitment of EPCs may be a powerful mechanism of endothelial repair and maintenance vascular function if development and progression of HF. Finally, GDF-15 is probably not good target for biomarkerguided therapy, although there are some investigations with opposite conclusions [24,25]. Although elevated level of GDF-15 associated with HF development, progression, and prognosis, there is not represented evidence regarding direct comparison of this biomarker with other clinical risk predictors and biomarkers [35].…”
Section: Introductionmentioning
confidence: 99%